Analytical formulas representing track-structure simulations on DNA damage induced by protons and light ions at radiotherapy-relevant energies - Kundrát, Pavel; Friedland, Werner; Becker, Janine; Eidemüller, Markus; Ottolenghi, Andrea; Baiocco, Giorgio (Scientific reports, 2020)
Track structure based simulations valuably complement experimental research on biological effects of ionizing radiation. They provide information at the highest level of detail on initial DNA damage induced by diverse types of radiation. Simulations with the biophysical Monte Carlo code PARTRAC have been used for testing working hypotheses on radiation action mechanisms, for benchmarking other damage codes and as input for modelling subsequent biological processes. To facilitate such applications and in particular to enable extending the simulations to mixed radiation field conditions, we present analytical formulas that capture PARTRAC simulation results on DNA single- and double-strand breaks and their clusters induced in cells irradiated by ions ranging from hydrogen to neon at energies from 0.5 GeV/u down to their stopping. These functions offer a means by which radiation transport codes at the macroscopic scale could easily be extended to predict biological effects, exploiting a large database of results from micro-/nanoscale simulations, without having to deal with the coupling of spatial scales and running full track-structure calculations.
Keywords: poškození DNA; Linear Energy Transfer; radioterapie; DNA Damage; metoda Monte Carlo; Protons; dvouřetězcové zlomy DNA; Humans; Radiotherapy; DNA Breaks, Double-Stranded; lidé; Monte Carlo Method; lineární přenos energie; protony